Strengthening timely detection and reporting of unusual respiratory events from health facilities in Yaoundé, Cameroon. Issue 2 (10th January 2020) - Alroy, Karen A.; Gwom, Luc Christian; Ndongo, Chanceline Bilounga; Kenmoe, Sebastien; Monamele, Gwladys; Clara, Alexey; Whitaker, Brett; Manga, Henri; Tayimetha, Carolle Yanique; Tseuko, Dorine; Etogo, Bienvenu; Pasi, Omer; et al.
Abstract: Background: The International Health Regulations state that early detection and immediate reporting of unusual health events is important for early warning and response systems. Objective: To describe a pilot surveillance program established in health facilities in Yaoundé, Cameroon in 2017 which aimed to enable detection and reporting of public health events. Methods: Cameroon's Ministry of Health, in partnership with the US Centers for Disease Control and Prevention, Cameroon Pasteur Center, and National Public Health Laboratory, implemented event‐based surveillance (EBS) in nine Yaoundé health facilities. Four signals were defined that could indicate possible public health events, and a reporting, triage, and verification system was established among partner organizations. A pre‐defined laboratory algorithm was defined, and a series of workshops trained health facilities, laboratory, and public health staff for surveillance implementation. Results: From May 2017 to January 2018, 30 signals were detected, corresponding to 15 unusual respiratory events. All health facilities reported a signal at least once, and more than three‐quarters of health facilities reported ≥2 times. Among specimens tested, the pathogens detected included Klebsiella pneumoniae, Moraxella catarrhalis, Streptococcus pneumoniae, Haemophilus influenza, Staphylococcus aureus, Pneumocystis jiroveci, influenza A (H1N1) virus, rhinovirus, and adenovirus. Conclusions: The events detected in this pilot were caused by routine respiratory bacteria and viruses, and no novel influenza viruses or other emerging respiratory threats were identified. The surveillance system, however, strengthened relationships and communication linkages between health facilities and public health authorities. Astute clinicians can play a critical role in early detection and EBS is one approach that may enable reporting of emerging outbreaks and public health events.